Three-dimensional giant invisibility to superscattering enhancement induced by Zeeman-split modes - G. P. Zouros; G. D. Kolezas; E. Almpanis; K. L. Tsakmakidis (ACS Photonics, 2021)
We report that the fundamental three-dimensional (3-D) scattering single-channel limit can be exceeded in magneto-optical assisted systems by inducing non-degenerate magnetoplasmonic modes. In addition, we propose a 3-D active (magnetically assisted) forward-superscattering to invisibility switch, functioning at the same operational wavelength. Our structure is composed of a high-index dielectric core coated by indium antimonide (InSb), a semiconductor whose permittivity tensorial elements may be actively manipulated by an external magnetic bias B0. In the absence of B0, InSb exhibits isotropic epsilon-near-zero (ENZ) and plasmonic behavior above and below its plasma frequency, respectively, a frequency band which can be utilized for attaining invisibility using cloaks with permittivity less than that of free space. With realistic B0 magnitudes as high as 0.17 T, the gyroelectric properties of InSb enable the lift of mode degeneracy, and the induction of Zeeman-split type magnetoplasmonic modes that beat the fundamental single-channel limit. Moreover, we show that chains of such particles, where each one operates in its superscattering regime, enable giant off-to-on enhancement in scattering efficiency, as well as unprecedentedly high forward scattering. These all-in-one designs allow for the implementation of functional and readily tunable optical devices.